PENINGKATAN KUANTITAS BAWANG MERAH (Allium cepa fa. ascalonicum, L. ) DENGAN BERBAGAI SUMBER KALIUM DAN BELERANG - Fatmawati Fatmawati; Yulia Eko Susilowati; Historiawati Historiawati (Universitas Tidar, 2018)
The research on increasing the quantity of shallots (Allium cepa fa. ascalonicum L.) with various sources of kalium and sulfur, conducted in July until September 2017 in Sawangan, Magelang. The latitude is 400 m, with the soils regosol and pH 5,6. The research used factorial experiment (3x3) arranged in a randomized complete block design, with three blocks. The first factor is the source of kaliumwich consists of three levels, without kalium, KCl and KNO3. The second factor is the source of sulfur wich consists of three levels, without sulfur, ZA and Petro-Cas. The result of the research show that KCl fertilizer increased longest leaf length, fresh weight of bulb per plot and dry weight of bulb per plot. KNO3 fertilizer increased fresh weight of bulb per plot, dry weight of bulb per plot, fresh weight of stover and dry weight of stover. ZA fertilizer increased longest leaf length, fresh weight of bulb per hill, dry weight keep thr bulb per hill, fresh weight of bulb per plot, dry weight of bulb per plot, fresh weight of stover and dry weight of stover. Petro-cas fertilizer not increased in all observation parameter. The combination of treatments of kalium and sulfur sources give the same results on the fresh weight of bulb per plot and dry weight of bulb per plot.